Submucosal tunneling endoscopic resection for large symptomatic submucosal tumors of the esophagus: A clinical analysis of 24 cases - Guo-Xiang Wang; Guang Yu; Yan-Li Xiang; Yang-De Miu; Hong-Gang Wang; Mei-Dong Xu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Studies evaluating submucosal tunneling endoscopic resection (STER) for the treatment of upper gastrointestinal submucosal tumors (SMTs) have recently increased. However, the efficacy and safety of STER for the treatment of large symptomatic SMTs in the esophagus have not been well investigated. The aim of the present study was to evaluate the efficacy and safety of STER for the treatment of large symptomatic SMTs in the esophagus.Methods: A total of 24 patients with large symptomatic SMTs in the esophagus who underwent STER in our hospitals between January 2015 and May 2018 were included in the study. The tumors were confirmed to be of muscularis propria layer origin. Treatment outcomes, complications, and follow-up results were retrospectively analyzed.Results: All 24 lesions were resected en bloc with STER. The mean maximum transverse diameter of the lesions was 4.7 (3.5–6.5) cm. The mean maximum longitudinal diameter of the lesions was 2.1 (1.5–3.0) cm. The mean duration from mucosal incision to complete mucosal closure was 65 (50–115) min. Postoperative pathological diagnosis confirmed 18 cases with leiomyomas, 4 cases with stromal tumors, and 2 cases with schwannomas. There were no major complications. There were no residual lesions or disease recurrence during follow-up.Conclusion: STER is safe and effective for the treatment of large symptomatic SMTs of muscularis propria layer origin in the esophagus.Cite this article as: Wang GX, Yu G, Xiang YL, Miu YD, Wang HG, Xu MD. Submucosal tunneling endoscopic resection for large symptomatic submucosal tumors of the esophagus: A clinical analysis of 24 cases. Turk J Gastroenterol 2020; 31(1): 42-8.